Modulação da excitabilidade de neurônios do Locus Coeruleus por receptores metabotrópicos de glutamato do grupo I - Jennifer Diniz Soares Guimarães (2017)
Metabotropic Glutamate Receptors are members of the G-protein-coupled receptors superfamily. These receptors are classified into three groups: Group I (mGlu1 e mGlu5), Group II (mGlu2 e mGlu3) and Group III (mGlu4, mGlu6, mGlu7 e mGlu8). We investigated the effects of activating Group I Metabotropic Glutamate Receptors (mGluR-I) on the excitability of Locus Coeruleus (LC) neurons. Whole-cell current clamp and voltage clamp experiments were performed on LC neurons in coronal slices (200 μM) of brainstem from Wistar rats. LC neurons presented spontaneous and rhythmic action potentials at a frequency of 1.8 ± 0.3 Hz (N=9). Application of the selective mGluR-I agonist, (S)-3-5-DHPG (DHPG, 10 μM), caused a increase in action potential firing rate of 210 ± 23% (p=0.004). The effect of DHPG was transient and action potential frequency recovered partially during application of agonist (i.e., the effect of DHPG desensitized). We tested if DHPG depolarized the neurons by measuring the peak of the all-points histogram of membrane potentials. This is the value of membrane potential at which Vm pauses briefly between action potentials. DHPG caused a small but significant increase in Vm (i.e., a small depolarization of the membrane potential) of 1.8 ± 0.03 mV (N=3, p=0.03). To determine if this small membrane depolarization could be responsible for the observed increase in action potential firing frequency, we measured action potential frequency and the resting potential while applying slow current ramps (from -30 to +30 pA over 10 s). These data allowed us to calculate the dependence of AP frequency on value of resting potential and we obtained a slope of 0.7 ± 0.1 Hz / mV (N=2). We conclude that the depolarization caused by DHPG can explain only part of the observed increase in action potential frequency. We next recorded membrane current under whole-cell voltage clamp to measure the DHPG-dependent current. DHPG caused a dosedependent inward shift in membrane current with an EC50 of 7.3 μM and a maximal effect of -35 pA. Like the effect of DHPG on action potential frequency, the DHPGdependent current desensitized with a time constant of ~100 s. This current was largely inhibited by the selective mGlu1 receptor antagonist LY367385 (160 μM), with no apparent effect of the mGlu5 antagonist MPEP (20 μM). Although differences in LC has been reported for female and male rats, we observed no dependence of sex on the size of the DHPG-dependent current. We conclude that activation of mGluR-I receptors changes the firing rate of these neurons through multiple mechanisms including depolarization of the membrane potential, generation of a steady-state inward current, and changes to pacemaker currents.